GEREJA DAN PENDIDIKAN SENI MUSIK BAGI ANAK - Ariel Januar Chrisnahanungkara (Tonika: Jurnal Penelitian dan Pengkajian Seni, 2019)
The purpose of this study is to understand the importance of carrying out music education by the church. This study explains the importance of art education for humans, the life of art in church and the process of art education that has been occurred in church. In particular, this study reminds us that church should not ignore music education in the church in an effort to maintain the church traditions.